Auditoría administrativa como herramienta para la evaluación de los procesos en la Unidad Ejecutora 407 Red de Salud Loreto - Nauta 2021 - Alarcon Sanchez, Larry (2022)
The general objective of this research was to determine the relationship between the administrative audit and the administrative processes in the Executing Unit 407 Health Network Loreto - Nauta 2020, therefore, an applied type study and non-experimental design has been chosen, to which has taken a sample of 10 people who were surveyed through a questionnaire. The work concludes that the administrative audit is related to the administrative process in a positive and significant way (r=0.930; sig.= 0.000); the same happens with planning (r=0.929; sig.= 0.000); the organization (r=0.788; sig.= 0.007); address (r=0.828; sig.= 0.003); and control (r=0.625; sig.= 0.043). At the same time, it was determined that the administrative audit is regular (30%), due to the fact that an analysis and preliminary study of the process that is intended to be evaluated is rarely carried out, likewise the information is sometimes interpreted for the preparation of the report, as well as It is almost never possible to distinguish different models of presentation of the report, finally, compliance with the recommendations is almost never verified. On the other hand, the administrative process is rated as regular (30%), this is because the allocation of resources never has a budget, the manuals of functions and procedures are sometimes updated, however, digital means are almost always established. for communication, but few mechanisms are established for performance evaluation.